Socio-Ecological Factors in Building a Healthy Community: A Comparative Study of Healthy Community Assessment Standards - Jiaying Zhao; Yang Chen; Pan Zhang (Buildings)
Healthy community assessment standards significantly influence community design and planning and are an important measure of a community’s ability to support health and well-being. Previous studies have mostly focused on built-environment indicators. However, building a healthy community is a complex issue involving multiple dimensions and factors. The consideration of the full range of health promotion factors is the key to determining their potential impact on individuals’ health. It is necessary to consider multiple perspectives to deepen the understanding of community health influences and enhance the effectiveness of the implementation of the assessment standards. The socio-ecological model (SEM) provides a critical framework for understanding the multiple influences on individual health. In this study, a two-dimensional interdisciplinary analytical framework of “socio-ecological factors–development goals” is developed by integrating development goals that summarize building considerations in assessment standards. Contextual analysis is used to examine the provisions of the following assessment standards: Assessment Standard for Healthy Community (ASHC), Assessment Standard for Healthy Retrofitting of Existing Residential Area (ASHRERA), WELL Community Standard (WELL), and Fitwel Certification System of Community (Fitwel). The results show that community and organization factors are used more than interpersonal and policy factors among the four standards. Humanistic constructions lack attention in the ASHC and ASHRERA standards compared with the other standards. The differences between the four standards indicate that there is a need to focus on regional features and develop locally adapted interventions. This study offers a novel exploration of the potential effectiveness of healthy community assessment standards from a multidisciplinary perspective. The results of this study support standard-setters and planners in the development of interventions to improve building healthy communities using intersectionality frameworks.